2023
DOI: 10.1002/hsr2.1341
|View full text |Cite
|
Sign up to set email alerts
|

Research on the socioeconomic factors that influence the development of voluntary, non‐remunerated blood donation in China—A correlation and regression analysis based on data from 2012 to 2018

Abstract: Background and Aims: Previous research has shown that socioeconomic factors, such as income and education, are associated with blood donation behavior. This study aims to investigate the factors that influence blood donation behavior using a large database of blood donation records and to provide further empirical evidence and insights into the factors that influence blood donation behavior and to identify potential strategies to increase blood donation rates in China.Methods: This study employed correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Interestingly, our study reveals a positive correlation between the students’ blood donation rate and their monthly living expenses. This finding resonates with Lin’s research, indicating a linear relationship between socioeconomic status and blood donation rate [ 5 ]. Studies indicate that individuals with higher socioeconomic status are more inclined towards altruistic behaviors, providing theoretical support for our findings [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, our study reveals a positive correlation between the students’ blood donation rate and their monthly living expenses. This finding resonates with Lin’s research, indicating a linear relationship between socioeconomic status and blood donation rate [ 5 ]. Studies indicate that individuals with higher socioeconomic status are more inclined towards altruistic behaviors, providing theoretical support for our findings [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…College and university students, often in good physical health and receptive to blood donation, represent a high-quality donor group [ 3 , 4 ]. Lin et al’s study identified a direct correlation between college enrollment and blood donation rates among individuals aged 18–34, emphasizing the pivotal role of education, particularly university education, in donation propensity [ 5 ]. Despite their potential, significant variations in blood donation [ 3 , 6 ] rates among college or university students exist across different Chinese cities (e.g., Jinan, 50.22%; Fuzhou, 38.67%; Shaoxing, 7.33%) [ 7 – 9 ], mirroring global disparities [ 3 , 4 , 10 12 ], indicating a universal blood donation strategy may yield limited effectiveness.…”
Section: Introductionmentioning
confidence: 99%